Kanre Juma: Tradisi Jumat Berkah di Wilayah Peri Urban Desa Kaballokang Pakkabba Kabupaten Takalar - Abdul Rahman (Journal of Urban Sociology, 2023)
Society is formed through a process of social relations that takes place on an ongoing basis between individuals and individuals, individuals and groups, and groups and groups. Interactions that occur continuously for a long time produce togetherness. In addition, social interaction also produces several patterns of shared relationships, shared values, social institutions and social care. In the context of rural communities, especially in Kaballokang Pakkabba Village, this social concern is manifested in the activity of sharing rice on Fridays (kanre juma). This study aims to elaborate in depth on the origins of the emergence of Kanre Juma and its function for society. This research was conducted using qualitative methods. Data was collected through observation and interviews. The results of the study showed that the division of the juma kanre was a continuation of people's habits during the Covid-19 pandemic. Kanre Juma in the perspective of functional theory has the functions of adaptation, goal attainment, integration and latency. The division of kanre juma has two dimensions in people's lives, namely as a form of worship that expects favor from God, and on the other hand it also strengthens family ties or social relations within the community.Keywords: generous, kanre juma, social solidarity